Education teachers at middle level: a case study on science teaching - Sofia Neumann; Dulce Maria Strieder (Universidad Distrital Francisco José de Caldas, 2018)
The debate about the importance of teacher education has been taking shape in a practice raised by theorists who deal with the importance of teaching work. This discussion covers, in addition to continued education, the initial training, that may occur at the undergraduate or high school in the "Normal" course. Humberto de Alencar Castelo Branco School - High School and Normal modality, in the municipality of Santa Helena, in the western region of the state of Paraná, offers the Training Course for Teachers of Early Childhood Education and Initial Years of Elementary School in the modality Normal. In order to verify if the students are prepared to act in the discipline of Sciences in the Initial Years, we carried out an investigation, through interviews with ten students who work in schools of the municipal network. Results showed that it is necessary to restructure the course in relation to the classes of the Teaching Methodology disciplines and the policies of distribution of classes for teachers should be re-evaluated.